The Anthocyanin, Phenolic Acid, Free Sugar, and Organic Acid Content of an Anthocyanin Extract from a Purple-fleshed Potato Cultivar ‘Synkeä Sakari’ - Lintala, Maisa (fi=Turun yliopisto|en=University of Turku|, 2018)
Anthocyanins might improve insulin resistance and decrease the levels of postprandial glucose. In a recent study purple-fleshed Finnish land race potato cultivar Solanum tuberosum L. ‘Synkeä Sakari’ was discovered to decrease insulinemia and glycemia in healthy males when compared to a yellow-fleshed potato. One of the reasons may be due to the anthocyanins that give the deep purple color to the tubers. An anthocyanin extract from the purple-fleshed potato cultivar ‘Synkeä Sakari’ was studied. The anthocyanins, phenolic acids, free sugars, and organic acids were investigated and determined. A single-blind randomized cross-over study with two potato meals separated by a minimum of two weeks of wash-out time was performed. Healthy adult male participants consumed a mashed yellow potato meal with and without the anthocyanin extract. Blood samples were drawn at various time points before and after consuming the study meal. The participants consumed standardized low flavonoid and low fiber meals 48 hours before and 24 hours after the test meal. The anthocyanins and the phenolic acids from the extract were identified with UV-vis spectrophotometer and UHPLC-MS method and quantified with HPLC-DAD. Free sugars and organic acids were identified and quantified with GC-FID. The extract contained anthocyanins and phenolic acids like petunidin, chlorogenic acid, and caffeic acid. The extract contained free sugars and organic acids like glucose, citric acid, and malic acid. Statistical analysis will be conducted for the glycemia and insulinemia results in another study to assess whether the addition of the anthocyanin extract from Synkeä Sakari to a yellow potato meal improve the glycemic and insulinemia response.